The Broken Bridge: Are Religious Courts Upholding the Promise of Post-Divorce Support for Women and Children in Indonesia? - Ahsanul Fahmi; Arlo Benjamin Scott; Souad Ahmed Ezzerouali; Sergi Fernandez Alejandro (Universitas Negeri Semarang, 2025)
Women and children occupy a distinct and vulnerable position within the Indonesian legal system, particularly in post-divorce situations. Although statutory provisions and Supreme Court regulations establish a normative foundation for protecting their rights, implementation remains inconsistent across judicial practices. This study examines the evolving role of the Religious Courts in ensuring the fulfillment of women’s and children’s rights after divorce. Using a normative juridical method with statute and conceptual approaches, the research explores the gap between legal norms and enforcement. Findings reveal that despite the limited number of divorce rulings explicitly addressing alimony, the Supreme Court has initiated significant reforms through Surat Edaran Mahkamah Agung (SEMA), strengthening judicial authority to defend vulnerable parties. Furthermore, innovative practices observed in the Religious Courts of Surabaya, Gresik, Bengkulu, and Bontang—such as salary deductions, digital monitoring systems, and inter-agency collaboration—demonstrate effective institutional interconnection in enforcing alimony. The novelty of this research lies in identifying an emergent model of cross-sectoral collaboration within the judiciary that bridges normative law and practical enforcement. Its primary contribution extends beyond the Indonesian context by offering an applicable framework for other jurisdictions facing similar challenges in the protection of women and children’s post-divorce rights. This study underscores that institutional synergy and digital governance can serve as globally relevant strategies for achieving sustainable legal protection and advancing social justice.